Eighty Percent of Patients With Surgical Hip Dislocation for Femoroacetabular Impingement Have a Good Clinical Result Without Osteoarthritis Progression at 10 Years - Steppacher, Simon D. (Clin Orthop Relat Res, 2014)
BACKGROUND: We previously reported the 5-year followup of hips with femoroacetabular impingement (FAI) that underwent surgical hip dislocation with trimming of the head-neck junction and/or acetabulum including reattachment of the labrum. The goal of this study was to report a concise followup of these patients at a minimum 10 years. QUESTIONS/PURPOSES: We asked if these patients had (1) improved hip pain and function; we then determined (2) the 10-year survival rate and (3) calculated factors predicting failure. METHODS: Between July 2001 and March 2003, we performed surgical hip dislocation and femoral neck osteoplasty and/or acetabular rim trimming with labral reattachment in 75 patients (97 hips). Of those, 72 patients (93 hips [96%]) were available for followup at a minimum of 10 years (mean, 11 years; range, 10–13 years). We used the anterior impingement test to assess pain and the Merle d’Aubigné-Postel score to assess function. Survivorship calculation was performed using the method of Kaplan and Meier and any of the following factors as a definition of failure: conversion to total hip arthroplasty (THA), radiographic evidence of worsening osteoarthritis (OA), or a Merle d’Aubigné-Postel score less than 15. Predictive factors for any of these failures were calculated using the Cox regression analysis. RESULTS: At 10-year followup, the prevalence of a positive impingement test decreased from preoperative 95% to 38% (p < 0.001) and the Merle d’Aubigné-Postel score increased from preoperative 15.3 ± 1.4 (range, 9–17) to 16.9 ± 1.3 (12–18; p < 0.001). Survivorship of these procedures for any of the defined failures was 80% (95% confidence interval, 72%–88%). The strongest predictors of failure were age > 40 years (hazard ratio with 95% confidence interval, 5.9 [4.8–7.1], p = 0.002), body mass index > 30 kg/m(2) (5.5 [3.9–7.2], p = 0.041), a lateral center-edge angle < 22° or > 32° (5.4 [4.2–6.6], p = 0.006), and a posterior acetabular coverage < 34% (4.8 [3.7–5.6], p = 0.006). CONCLUSIONS: At 10-year followup, 80% of patients with FAI treated with surgical hip dislocation, osteoplasty, and labral reattachment had not progressed to THA, developed worsening OA, or had a Merle d’Aubigné-Postel score of less than 15. Radiographic predictors for failure were related to over- and undertreatment of acetabular rim trimming. LEVEL OF EVIDENCE: Level IV, therapeutic study.